The Effect of Viral Marketing and Flash Sale on Impulsive Buying on Wardah Products on The Tiktok Shop Marketplace (Case Study on Students of Management Program, Undikma) - Ajizah Nuramalia; Menik Aryani; Ira Dianti (Universitas Pendidikan Mandalika, 2025)
Wardah is a product that is always Viral when releasing the latest product and always provides a Flash Sale during live streaming on the Tiktok Shop application, thus the author conducted a study related to